2006
DOI: 10.1029/2005jd006901
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variations in surface solar irradiance as observed in a globally remote network

Abstract: [1] Twenty-eight years of surface solar irradiance observations at five remote climate observatories are analyzed for long-term temporal variations and spatial representativeness. Autocorrelated temporal variations are suggested in the annual mean irradiance records at some of the sites and in normalized anomaly records for various combinations of the surface sites. These variations are illustrated by first-, second-, and third-degree polynomials as well as by a sinusoidal fit, all of which are used as data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 32 publications
4
87
1
1
Order By: Relevance
“…These type of methods have been used in many practical applications (e.g. Zhang et al, 2004;Dutton et al, 2006;Wild et al, 2006;and Hinkelman et al, 2009 M3: Missing data and data flagged in M2 were filled from an interpolated zenith angle-dependent fill dataset that was built from available observations from the same two-week interval in which the missing data are located. The fill data therefore account for both the diurnal (zenith angle) and seasonal variation.…”
Section: Methods For Monthly Mean Computationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These type of methods have been used in many practical applications (e.g. Zhang et al, 2004;Dutton et al, 2006;Wild et al, 2006;and Hinkelman et al, 2009 M3: Missing data and data flagged in M2 were filled from an interpolated zenith angle-dependent fill dataset that was built from available observations from the same two-week interval in which the missing data are located. The fill data therefore account for both the diurnal (zenith angle) and seasonal variation.…”
Section: Methods For Monthly Mean Computationsmentioning
confidence: 99%
“…Roesch et al: Assessment of BSRN radiation records for the computation of monthly means to monitor changes in the radiation balance from both the surface and space. More and more studies, particularly those based on surface observations, present evidence that the radiative fluxes are not stable over time but undergo significant decadal variations (e.g., Gilgen et al, 1997;Stanhill and Cohen, 2001;Liepert, 2002;Dutton et al, 2006;Wild, 2009 and references therein), which may have major consequences for the climate system and climate change (Wild, 2009). However, all these analyses rely on data (typically monthly or yearly means), that have been aggregated in some way or another from incomplete raw data with much higher temporal resolution (typically minute to hourly).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are given in Table 2 and Figure 3. Although pyranometer records can be representative for a larger region (examples are given by Dutton et al [2006]), the spatial coverage of ground-based pyranometer records cannot compete with satellite records. Advantages of the pyranometer data are, however, (1) their reaching back in presatellite times and (2) their temporal stability due to slow but continuous improvements of instruments and calibration procedures over the observational period.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…[6] As soon as pyranometer measurements for the 1990s had become available, the SWIR was reanalyzed: Wild et al [2005] found a widespread increase of SWIR since the late 1980s and Dutton et al [2006] found, in the period from 1976 through to 2004, a decrease followed by an increase in three records of SWIR (those for South Pole, American Samoa and Boulder, Colorado).…”
Section: Introductionmentioning
confidence: 99%